The Role of the Palangka Raya City Government in Promoting the Halal Economic Ecosystem - Wendy Wiraganti, Risna; Syarifuddin; Khair, Abdul; Patrajaya, Rafik (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2025)
This study examines the strategic role of the Palangka Raya City Government and the awareness level of business actors in developing a halal economic ecosystem in Central Kalimantan. Using a qualitative approach through literature studies, interviews, and observations, this research is based on the Sustainability Governance Theory to analyze the continuity of regulations in supporting the halal economy, as well as the Fraud Pentagon Theory (Crowe Howarth, 2012) to identify obstacles in the implementation of halal certification based on five elements: pressure, opportunity, rationalization, capability, and arrogance. The halal economic ecosystem in Central Kalimantan is influenced by two main factors. First, government intervention remains dominant due to the low independent initiative of business actors in obtaining halal certification. Second, medium-sized business actors are more aware of halal certification as both a legal obligation (juridical imperative) and a strategic investment to enhance competitiveness. From the perspective of the Fraud Pentagon Theory, pressure arises from regulatory demands and market preferences, while weak opportunity in supervision creates loopholes for the circulation of uncertified products. Medium-sized businesses have a higher level of rationalization regarding halal certification compared to micro and small enterprises, as they view it as a quality assurance and business investment. Capability is a challenge for UMKM with limited resources, whereas arrogance is observed among business actors who consider certification unnecessary. This study explores the impact of low business awareness, limited policy support, and restricted access to halal certification within the framework of the Five Pentagon Assets. The deficit in human capital is reflected in the lack of understanding among business actors, while the constraints in financial and social capital are evident in the lack of incentives and regulatory support. The sustainability of halal certification depends on strengthening these five assets through policy harmonization, optimizing awareness, and increasing the independence of business actors in consistently meeting halal standards. Keywords : Halal Ecosystem, Government Role, Halal Certification.